Prevalence of Eating Disorders among Female College Students of Northern Broader University, Arar, Kingdom of Saudi Arabia - Fatima, Waseem; Fatima, Rizwan; Anwar, Nida Suhail (International Journal of Child Health and Nutrition, 2018)
Objective: The study aimed at examining the prevalence and correlates of eating disorder among female college students of Northern Broader University, Arar city, Kingdom of Saudi Arabia. Methods: A cross sectional survey was conducted among female college students. The total sample size was 160 (66.66% of total population of college) and stratified random sampling technique was used to select female students age ranged between 18 and 23 years from faculty of medical and faculty of applied medical science. Subjects were ask to fill pre tested questionnaire about socioeconomic status, age at menarche, body image and Eating attitude test 26 (EAT 26), there height and weight were measured and BMI was calculated. Results: Out of 160 female college students only 120 (75%) returned completely filled questionnaires and they were considered for statistical analysis. It was found that, 32 (26.66%) of study population scored 20 or above, which is the cutoff point of EAT-26, indicating negative eating attitudes. There was significant difference found in prevalence of disordered eating attitudes in different BMI ranges. However, the association between student’s age at menarche and abnormal eating attitude was not statistically significant. Conclusion: The findings support our hypothesis of a relatively high rate of abnormal eating attitudes (as reflected by high EAT-26 score) in this population. The results have important implication for increasing awareness about an emerging clinical problem. The prevalence of eating disorder is the most useful measure for planning health care facilities, as it indicates the demand for care.